Sistem Rancangan Pendataan Yatim, Fakir Miskin dan Lansia pada Kantor Desa Baet Kecamatan Baitussalam Kabupaten Aceh Besar - Muhammad Zuhri; Muhammad Wali; Harry Idwan (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2023)
This study discusses the design of a data collection system for orphans, the poor, and the elderly at the Baet Village Office, Baitussalam District, Aceh Besar. The problem discussed is how to use computer technology to enter data into the data collection system. The purpose of this study was to determine the use of the data collection system. The data for this study were collected through a literature study which involved reviewing books and materials related to the topic. In addition, field studies were also carried out by conducting interviews and direct observation of objects related to this research report. Apart from that, in this study, the authors also utilized the Extreme Programming (XP) method in the process of developing a data collection system. The XP method is an Agile method that enables adaptive, collaborative, and iterative software development. The results showed that the use of computer technology and the XP method in the development of a data collection system was able to speed up the process of collecting and processing data, as well as increasing work efficiency and effectiveness. In addition, the developed data collection system is also able to produce more accurate and integrated data, so that it can assist the village government in planning and making more appropriate decisions related to community services, especially orphans, the poor, and the elderly.